2010
DOI: 10.1007/s00259-010-1408-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional lymph node involvement in T1 papillary thyroid carcinoma: a bicentric prospective SPECT/CT study

Abstract: LNM occurs in one quarter of all patients with T1 PTC, and also in the subset with microcarcinoma. Performing (131)I SPECT/CT, either with therapeutic or diagnostic radioactivities, directly after thyroidectomy should provide more accurate staging of T1 PTC, thus facilitating optimal therapeutic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 10 publications
9
39
0
6
Order By: Relevance
“…In a large, bicentric study of 151 patients, using a combination of nodal staging based on histopathology (pN1) information (in 46% patients who underwent surgical neck dissection) and imaging information (SPECT/CT in 54% patients who did not undergo neck dissection), Mustafa et al reported that nodal metastases occurred in 26% of T1 tumors and in 22% of microcarcinomas (T1a tumors, #1.0 cm). Regarding nodal staging, SPECT/CT was more accurate than planar imaging in 24.5% of patients (46).…”
Section: Utility Of Post-therapy Radioiodine Spect/ctmentioning
confidence: 95%
“…In a large, bicentric study of 151 patients, using a combination of nodal staging based on histopathology (pN1) information (in 46% patients who underwent surgical neck dissection) and imaging information (SPECT/CT in 54% patients who did not undergo neck dissection), Mustafa et al reported that nodal metastases occurred in 26% of T1 tumors and in 22% of microcarcinomas (T1a tumors, #1.0 cm). Regarding nodal staging, SPECT/CT was more accurate than planar imaging in 24.5% of patients (46).…”
Section: Utility Of Post-therapy Radioiodine Spect/ctmentioning
confidence: 95%
“…In recent years, it has been shown that the analysis of SPECT-CT images helps to precisely localize focal iodine uptake and to characterize it as either normal or abnormal. In postablation setting, neck and thorax SPECT-CT improves the N staging of patients with DTC (4,9). SPECT-CT data may also reduce the need for additional cross-sectional imaging in 20% of patients and alter the ATA risk of recurrence classification in 6% of patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…GBq (30-260? mCi) [20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Radioiodine SPET-CT was used for surveillance for thyroid cancer recurrence, before I-131 therapy [19,20,27,41,42], in the post-surgical setting for radioiodine ablation of normal thyroid remnants, [21,22,24], or in post-therapy imaging [25-30, 32, 33, 36, 37, 39, 40, 43-45].…”
Section: Study Characteristics and Protocols For Spet-ctmentioning
confidence: 99%
“…Impact of SPET-CT on thyroid cancer staging, management and prognosis Accurate staging and risk stratification are critical considerations in the management of thyroid cancer. Post-therapy I-131 SPET-CT studies [20,25,26,30,33,37,40] and follow-up diagnostic scans after thyroid remnant ablation [19,41] have demonstrated improved characterization of nodal (N) and distant metastases (M) status on TNM staging schema. At the first radioablation therapy, posttherapy SPET-CT was found to restage the cervical N status in 20/57 (35 %) patients [33].…”
Section: Comparison With Other Imaging Modalities In Thyroid Cancermentioning
confidence: 99%